Portable landscapes: flexibility and customization associated with temporary landscapes - Sickmann, Jared (Kansas State University, 2016)
Cities and towns across the world are in a dynamic state of change, and therefore, becoming responsive to new and innovative approaches to creating and restoring public spaces. These new approaches address the need for flexible, multifunctional spaces in order to adapt to and accommodate the changing demands and unexpected circumstances that occur within the city (Wall 1999, Temel 2006, Gehl 2011). Temporary landscapes, or site specific, time-limited designs of open space, have become an emerging approach to improving public spaces. These small scale projects provide unique experiences and offer a laboratory for experimentation where new, innovative ideas can be tested (Lydon 2012, Sargin and Savas 2012, Temel 2006). The idea of flexibility and the need for multifunctional spaces are explored through the following report by investigating how an innovative approach involving temporary landscapes can enhance streetscape quality and offer a variety of public activities. First, I developed a deeper understanding of temporary landscapes in order to identify the transition in approach to urban design from focusing on permanence to temporary, and express the importance of temporality in urban design. A design matrix exploring programmatic options and customizable design features was established through an extensive literature review and case study analysis. Through the application process, I explored the regulatory process involved in implementing a temporary landscape intended for the Aggieville Business District in Manhattan, Kansas. This procedure involved a review of the city's ordinances and liability concerns, designing a portable landscape, and constructing a prototype to be deployed off-street until approval is gained. The results from this project provide field evidence to support recommendations for future design iterations for portable landscapes that increase pedestrian comfort and support an expanded range of activities for public spaces. Prototypes of different design iterations and replications can also serve as future projects for the College of Architecture, Planning, and Design at Kansas State University. Ultimately, this project will begin a critical discussion of the future role of temporary landscapes in cities that are in a dynamic state of change.
Keywords: Temporary Landscapes; Urban Design; Multi-functional Spaces; Portable Landscapes; Streetscape